2021
DOI: 10.3390/met11071066
|View full text |Cite
|
Sign up to set email alerts
|

New Ti–35Nb–7Zr–5Ta Alloy Manufacturing by Electron Beam Melting for Medical Application Followed by High Current Pulsed Electron Beam Treatment

Abstract: High-current pulsed electron-beam (PEB) treatment was applied as a surface finishing procedure for Ti–35Nb–7Zr–5Ta (TNZT) alloy produced by electron beam melting (EBM). According to the XRD results the TNZT alloy samples before and after the PEB treatment have shown mainly the single body-centered cubic (bcc) β-phase microstructures. The crystallite size, dislocation density, and microstrain remain unchanged after the PEB treatment. The investigation of the texture coefficient at the different grazing angle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
4
11
0
Order By: Relevance
“…Thus, by comparison, it can be observed that the proposed materials have registered values of corrosion rates that are of 1000 times smaller than 0.02 mm/y, indicating their potential use as implantable biomaterials. Likewise, similar results of the corrosion parameters have also been reported by Surmeneva, M. et al [26], which have developed a TNTZ alloy by electron beam melting technique.…”
Section: Corrosion Testing Of Tntz Alloy In Sbfsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, by comparison, it can be observed that the proposed materials have registered values of corrosion rates that are of 1000 times smaller than 0.02 mm/y, indicating their potential use as implantable biomaterials. Likewise, similar results of the corrosion parameters have also been reported by Surmeneva, M. et al [26], which have developed a TNTZ alloy by electron beam melting technique.…”
Section: Corrosion Testing Of Tntz Alloy In Sbfsupporting
confidence: 87%
“…Nb and Ta are β stabilizers and Zr is important for the solid solution strengthening of the alloy. In the last decades, the properties of new metastable beta Ti alloys have been intensively studied: Ti-35Nb-7Zr-5Ta [26], Ti-24Nb-4Zr-8Sn [27], Ti-25Ta-25Nb [28], and Ti-20Zr-10Nb [29].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Young's modulus of these materials significantly differs from that of the human bones, which can cause the resorption of adjacent bone tissues [7]. The ideal implant should exhibit low Young's modulus (very close to that of the human bones), excellent wear resistance, and biocompatibility [8]. The discussed requirements for the implant material depend mostly on the surface properties of the alloys, and therefore, can be achieved by an appropriate technique for surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD patterns of the E-PBF-manufactured TNZT alloy are represented by clear (110), (200), (211), and (220) peaks (Figure b), which correspond to the β Ti phase (JCPDS file # 03-065-9438) with a bcc structure, with the following average lattice parameters: a = 3.2958 ± 0.0006 Å. In addition, the weak peaks at 2θ values of 34.04, 35.67, and 60.15° were detected, which can attribute to the small presence of α″ martensite and NbTi 4 (JCPDS file #03-065-7479) intermetallic phases in the orthorhombic crystal structure (the space group Cmcm ). , It is in good agreement with our previously reported results in ref of the TEM study of the as-manufactured TNZT alloy, which have shown the presence of the equiaxed β-grains with the fine dispersion of nanocrystalline α″ and NbTi 4 phases together with β-Ti twins.…”
Section: Resultsmentioning
confidence: 96%
“…Cuboid test samples with the dimensions of about 10 × 10 × 10 mm 3 were manufactured using the following processing parameters: the thickness of the layer (δ) was 100 μm, process temperature ( T ) settings (initial start plate preheat and process target temperatures) varied from 520 to 610 °C, beam current ( I ) was 3 mA, beam velocity ( v ) was 407 mm/s, line offset ( h , spacing between hatch lines in a raster type scan) was 0.1 mm, and area energy ( E A ) was 4.4 J/mm 2 . These settings provided the best physical and mechanical characteristics of the fabricated samples and were set based on the previously reported results . That study was mainly focused on the effects of high-current pulsed electron-beam (PEB) treatment as a surface finishing procedure on the TNZT alloy produced by E-PBF.…”
Section: Theoretical Methods and Experimental Proceduresmentioning
confidence: 99%